Challenges and Opportunities of Online Learning Modality: Experiences of Social Science College Teachers in a Philippine Private School - Lazaga, Tony; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Online learning has become a popular teaching modality used by educational institutions worldwide due to the threat of the Covid-19 pandemic. The paper intends to describe the experience of Social Science teachers in the conduct of online classes in a private school in Southern Negros in the Philippines. The study used phenomenological research to inquire about the online class experience of four social sciences instructors. The researcher employed the Realistic Phenomenological research design via an in-depth interview technique to elicit responses relevant to the topic and used the three C’s of Lichtman to generate the themes from the units of relevant meanings extracted from the interview transcripts. The findings reveal that they experienced challenges and opportunities in conducting the online class. The challenges include loss/Lack of internet connections, confusion and adjustments, Lack of motivation from the students to learn, and forming students to become lazy. On the other hand, online teaching helps teachers learn the new technology, flexibility of time and locations, diverse and enriching experience, online resources accessibility, and collaboration among colleagues.